A familial case of pulmonary arterial sequestration. Issue 2 (1st February 2000) - Dyer, J D; Anderson, J M; John, P R
Abstract : The cases of a mother and infant son are reported, both with a rare type of pulmonary sequestration where the arterial supply to the lung arises from the systemic circulation. This is a familial case of arterial sequestration. In both patients, the lung parenchyma was radiologically normal.